Personal identity and eastern thought - Correia Carlos João (Filozofija i Društvo, 2009)
This paper aims to show that the problem of personal identity is a fundamental question of the classical Indian thought. Usually we tend to think that personal identity is a Western philosophical subject, and so we tend to forget the significance of the Self (Atman) in Hinduism and even in Buddhism. The author shows how the Indian thought approached the question of personal identity and which was the singular solution outlined in the work consensually attributed to Gotama, the Buddha.